PHENYLPROPANOID GLUCOSIDES FROM CLERODENDRUM PHILIPINUM - Oanh, Hà Vân; Sinh, Phạm Xuân; An, Nguyễn Thái; Hùng, Tạ Mạnh; Minh, Châu Văn; Thảo, Nguyễn Phương; Kiện, Phan Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARYFrom the methanolic extract of the roots of Clerodendrum philipinum four phenylpropanoid glucosides were isolated by various chromatography methods. Their structures were identified as clerodenoside A (1), martynoside (2), acteoside (3), and isoacteoside (4) by means of spectroscopic methods including 1D-, 2D-NMR, and MS in comparison with previous literature data. Compounds 2-4 were found for the first time from the Crolerodendrum species.Keywords: Clerodendrum philipinum, phenylpropanoid glucoside